Molecular characterization of Citrobacter freundii, Edwardsiella tarda and Aeromanas hydrophila isolated from red tilapia (Oreochromis sp.) fingerlings cultured at Terengganu and Selangor - Wee, Wendy (Fakulti Sains dan Teknologi, 2010)
Red tilapia has been an important food fish that ranked on top of all freshwater aquaculture species in Malaysia. Nevertheless, productivity and sustainability of the red tilapia can be affected once diseases struck. In present study, phenotypic and genotypic characterization of fish disease causative agents has been focus on Citrobacter freundii, Edwardsiella tarda and Aeromonas hydrophila. A total number of 45 isolates were obtained from red tilapia fingerlings farmed at Terengganu and Selangor. Presumptive isolation of C. freundii, E. tarda and A. hydrophila has been made from moderate dark pink colony on Cefsulodin-Irgasan-Novobiocin (CIN) agar, tiny clear transparent colony with black dot on Xylose-Lysine-Deoxycholate (XLD) agar, and moderate yellow colony on Glutamate Starch Phenol red (GSP) agar, respectively. Meanwhile, bacterial identification was accomplished by 52 biochemical and physiological tests by conventional method and BBL Crystal™ Enteric/ Nonfermenter Identification Systems (E/NF ID). The production of hemolysins which lysed on blood agar has been regarded as strong evidence of pathogenic potential in A. hydrophila isolated from Terengganu farm despite that majority of the isolates were lack of hemolytic activity